Digital diaspora, reinvigorating Indigenous identity and online activism: social media and the reorientation of Rotuman identity. Issue 1 (November 2018) - Titifanue, Jason; Varea, Rufino Robert; Varea, Renata; Kant, Romitesh; Finau, Glen
The island of Rotuma in Fiji poses a paradox. Indigenous Fijians make up more than 60% of Fiji's population. However, as a unique ethnic group, Rotumans are a demographic minority, with their language listed on the UNESCO list of endangered languages. This is caused by extensive outmigration, with more than 80% of Rotumans residing outside of Rotuma. Recently, Rotuman migrants have heavily relied on Information and Communication Technologies (ICTs) and new media, as tools for reinvigorating culture, rekindling familial ties and being a platform for political discourse on Rotuman issues. Facebook has been increasingly employed by Rotumans to inform and educate themselves and their networks on the implications of two bills introduced in Fiji's Parliament in 2015, which impact Rotuma in terms of its land and customs. This article examines how Rotumans have innovatively used social media to reinvigorate culture and how this has evolved to take on an increasingly political dimension.